THE EFFECT OF GAMIFICATION INTERACTIVE LEARNING MEDIA ON MOTIVATION AND SCIENCE LEARNING OUTCOMES - Beny Irawanto; Triwahyudianto; Roni Alim Ba’diya Kusufa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effect of interactive gamification learning media on motivation and learning outcomes in the Natural and Social Sciences (IPAS) subject of elementary school students. The background of this study is the low motivation of students to learn and less than optimal learning outcomes that are often caused by learning media that are less innovative and interesting. The research method used is quantitative with a quasi-experimental design using a control group and an experimental group. The subjects of the study were elementary school students taking the IPAS subject. Data were collected through test instruments to measure cognitive learning outcomes and questionnaires to measure the level of student learning motivation. Data analysis techniques assisted by SPSS 26.0 for windows, with quantitative methods. Data were analyzed using descriptive statistics and paired t-tests. The results of the study showed that there was a significant effect of the use of interactive gamification learning media. Specifically, the experimental group that used gamification media showed an increase in learning motivation that was statistically higher than the control group. In addition, the cognitive learning outcomes of students in the experimental group also showed a significantly higher average value, indicating the effectiveness of gamification media in improving understanding and mastery of IPAS concepts.